NUMERICAL SIMULATION OF RESIDUAL STRESS IN UNDER-MATCHED WELDED JOINT BASED ON EQUAL-LOAD THEORY BY 3D FEM - QIAN YuWen; ZHAO JianPing (Jixie qiangdu)
Simulate and analyze the multi-pass welds in under-matched welded joint between CF62 and 316 L stainless steel with element birth and death technology by 3D finite element method. Design the under-matched welded joint based on equal-load theory. Found the multi-pass welds in under-matched welded joint whose shape is normal symmetrical X and the under-matched joint based on equal-load theory. The results show that the under-matched welded joint can reduce the residual stress compared with the normal well-matched welded joint. The under-matched joint based on equal-load theory has a smaller residual stress than the normal under-matched welded joint does so that it can improve the load capacity when it is used so the under-matched welded joint based on equal-load is more advantageous.